Curriculum transformation: An ODeL Case in South Africa (Perspectives in Education, 2020)
Despite the worldwide interest on transforming curricula, a case study examination of what really happens within an ODeL South African university context, has been much limited. By using psycho-social and social identity theory, we highlight the complexities involved in the process of transforming decades of teaching and learning practices. The reports from five colleges highlighted three key themes namely curriculum responsiveness, decolonization and identity issues. From these we developed a framework to help capture some of the complexities, identified implications and charted a new direction for future studies within the South African post-colonial and post-apartheid arena.